Reflections on criminal policy and deliberative democracy in habermas - Mota, Maria Nazareth Vasques; Mota, Guilherme Gustavo Vasques; Thomas, Carla (Seven Editora, 2024)
This article sought to conceptualize the Criminal Policy and its elaboration based on the thought of classic authors in the criminal area. The objective was to reflect on changes in the way of thinking and applying the Brazilian criminal legislation, that is, if the changes defended at the time were considered, if there was participation of civil society and jurists to change the way of punishing that is effective in relation to the poor, blacks and young people from the periphery, Habermas' thought was also considered in relation to the democratic perspective. DOI:https://doi.org/10.56238/sevened2024.010-054